Monitoring of hemostatic parameters for early prediction of first-trimester miscarriage. (18th August 2021) - Jiang, Limei; Du, Yingjian; Lu, Yi; Wu, Xuelian; Tong, Xuedong
Abstract: Background: Hypercoagulation starts as early as the first-trimester pregnancy and is a risk factor for thromboembolic events which are associated with miscarriage. Our study aimed to investigate coagulation, platelets, and fibrinolysis parameters alteration amongst trimester-specific normal pregnancy and first-trimester miscarriage patients. We also test the accuracy of haemostatic parameters determination for prediction of first-trimester miscarriage. Methods: Retrospective investigation of 50 women whose most recent pregnancy had ended in the first trimester and 54 age-matched consecutive normal pregnancy between 2016 and 2019. Furthermore, 51 non-pregnant, age-matched women were included in parallel to healthy controls. Twelve screening tests for coagulation and platelet parameters were assessed. Results: We found plasma levels of aPTT, FBG, and TT were significantly prolonged or decreased in miscarriage subjects than the corresponding first phase in normal pregnancies. PT, INR, aPTT, and d -dimer all shift back to normal in miscarriage patients compared with non-pregnant women. Shortened aPTT combined with TT and FBG can predicted the occurrence of first-trimester miscarriage with an AUC of 0.831. Conclusions: Routine assessment of aPTT combined with TT and FBG is a low-cost, widely available marker for prediction of first-trimester miscarriage.